2021
DOI: 10.1111/aji.13407
|View full text |Cite
|
Sign up to set email alerts
|

Association of circulating monocyte chemoattractant protein‐1 levels with polycystic ovary syndrome: A meta‐analysis

Abstract: Problem: Polycystic ovary syndrome (PCOS) is a common hormonal disorder that has a huge impact on the human infertility. Increased levels of various circulating inflammatory cytokines have been observed in PCOS patients, which can contribute to the pathogenesis of PCOS. Monocyte chemoattractant protein-1 (MCP-1), a secretory chemokine, is a potent chemotactic factor that recruits monocytes/macrophages to inflammatory foci. Several previous studies comparing the circulating MCP-1 levels between non-PCOS and PCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
(150 reference statements)
0
8
0
Order By: Relevance
“…Previous animal studies showed that C-reactive protein (CRP), white blood cell count (WBC), leukocyte factor 18 (IL-18), leukocyte factor 6 (IL-6), leukocyte factor 1 (IL-1β), monocyte chemotaxis protein-1 (MCP-1), tumor necrosis factor α (TNF-α) and macrophage inflammation protein-lα (MIP-lα) levels were significantly elevated in PCOS rats. Similar abnormalities in these parameters were also demonstrated in the PCOS group compared to the control group after adjustment for patient age and body mass index (BMI) (Cirillo et al, 2019;Bannigida et al, 2020;Rudnicka et al, 2020;Wu et al, 2021).…”
Section: Anti-inflammatory Effects and Nf-κb Inhibitionmentioning
confidence: 62%
“…Previous animal studies showed that C-reactive protein (CRP), white blood cell count (WBC), leukocyte factor 18 (IL-18), leukocyte factor 6 (IL-6), leukocyte factor 1 (IL-1β), monocyte chemotaxis protein-1 (MCP-1), tumor necrosis factor α (TNF-α) and macrophage inflammation protein-lα (MIP-lα) levels were significantly elevated in PCOS rats. Similar abnormalities in these parameters were also demonstrated in the PCOS group compared to the control group after adjustment for patient age and body mass index (BMI) (Cirillo et al, 2019;Bannigida et al, 2020;Rudnicka et al, 2020;Wu et al, 2021).…”
Section: Anti-inflammatory Effects and Nf-κb Inhibitionmentioning
confidence: 62%
“…According to some research, elevated MCP-1 mRNA expression has been seen in THP-1 human mononuclear macrophages, which suggests that inflammatory factors are present in PCOS patients' serum (72). As a result, other investigations have found According to a meta-analysis study, PCOS patients have substantially higher levels of MCP-1, which are unrelated to people's BMI (73). In this research, CRP, MCP1, and IL-18 gene expression were found to be significantly higher in the estradiol valerate group compared to the control group, indicating inflammation in mice with PCOS.…”
Section: Discussionmentioning
confidence: 98%
“…The primary biological function of MCP-1 is to recruit monocytes, neutrophils, and lymphocytes to the effector site to produce an inflammatory response. A recent meta-analysis of 11 studies including 529 PCOS patients showed that the level of MCP-1 was significantly increased in PCOS patients, with no significant difference between obese and non-obese PCOS patients (8). TNF-α is a cytokine produced in the acute phase of the body's inflammatory response.…”
Section: Discussionmentioning
confidence: 99%